Regulation, Communication, and Functional Roles of Adipose Tissue-Resident CD4+ T Cells in the Control of Metabolic Homeostasis - Zhou, Haiyan; Liu, Feng (Frontiers in Immunology, 2018)
Evidence accumulated over the past few years has documented a critical role for adipose tissue (AT)-resident immune cells such as CD4+ T cells in the regulation of local and systemic metabolic homeostasis. In the lean state, visceral adipose tissue (VAT) is predominated by anti-inflammatory T-helper 2 (Th2) and regulatory T (Treg) cell subsets. As obesity progresses, the population of Th2 and Treg cells decreases while that of the T-helper 1 (Th1) and T-helper 17 (Th17) cells increases, leading to augmented inflammation and insulin resistance. Notably, recent studies also suggest a potential role of CD4+ T cells in the control of thermogenesis. In this review, we have summarized recent advances in understanding the characteristics and functional roles of AT-resident CD4+ T cell subsets during obesity and energy expenditure. We have also discussed new findings on the crosstalk between CD4+ T cells and local antigen-presenting cells (APCs) including adipocytes, macrophages and dendritic cells (DCs) to regulate AT function and metabolic homeostasis. Finally, we have highlighted the therapeutic potential of targeting CD4+ T cells as an effective strategy for the treatment of obesity and its associated metabolic diseases.